FAKTOR–FAKTOR YANG BERHUBUNGAN DENGAN BAYI BERAT LAHIR RENDAH DI KABUPATEN TAPANULI UTARA TAHUN 2022 - Titin Hutasoit; Kesaktian Manurung; Jasmen Manurung (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2023)
Infant mortality is related to the weight of the newborn. The weight of a newborn is a benchmark used to assess the degree of public health. If a newborn weighs less than 2500 grams, it is called a low birth weight baby (LBW). The causes of LBW are many and varied. Internal and external factors of the mother, fetus and other factors such as behavior. This study will examine the factors associated with Low Birth Weight Babies (LBW) in North Tapanuli Regency in 2022. This study is a cross-sectional study with a total sample of 34 people (total sampling). The results of the univariate test showed that 25 mothers gave birth to LBW and 9 LBW mothers. The results of the bivariate test showed that there was a relationship between parity, pregnancy distance and exposure to health information media with LBW. The results of the multivariate test showed that there was a significant effect between parity and the incidence of LBW with an OR value of 13,141, meaning that mothers with high parity had a 13,141 greater chance of having low birth weight in North Tapanuli Regency. The role of the family and posyandu is highly expected. Socialization and family planning campaigns are enhanced through the use of print, electronic, and social media.